Some Physiological Changes of Metronidazole Used to Treat Giardia lamblia in Human - Abbass, S. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study aimed to introduce the effect of Giardia lamblia infection on changes in some biochemical parameters in serum of infected patients before and after treatment during a period of one year, (from Feb, 2008 to Jan, 2009).Samples of 50 infected patients who referred to Al-Kadimiyah Teaching Hospital, were collected before and after 7 days of treatment.The activity of liver enzymes (Gpt and Got) before treatment increased significantly as it reached up to (8.47) u/L and 19.06 u/L, comparing with control values (6.455) u/L and (8.39) u/L respectively. The activity of the enzymes decreased after treatment but the values of Gpt and Got remained higher than the control values as reached 7-27 u/L, 11-64 u/L.The concentration of creatinine before treatment significantly increased slightly (p